2015
DOI: 10.3906/sag-1406-74
|View full text |Cite
|
Sign up to set email alerts
|

Determining the health beliefs and breast cancer fear levels ofwomen regarding mammography

Abstract: Background/aim: Women's fears and health beliefs impact their participation in early breast cancer diagnosis approaches. This study was conducted to determine the health beliefs and fear levels of women older than 50 regarding mammography. Materials and methods:A cross-sectional study was conducted in Turkey. The study cohort consisted of 300 women selected by cluster sampling who agreed to participate in the study. A health belief model scale and breast cancer fear scale were used in data collection. Descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
3
20
0
3
Order By: Relevance
“…Concerning marital status, the study findings indicated that there was no significant association between MS utilization and marital status. These findings are similar to finding of Abdelaziz et al, (18) and Secginli et al (25) In the present study, education was not significantly associated with MS utilization; Ersin et al, (26) found that there was no difference detected between the educational level and the rate of having mammograms. They concluded that higher education does not mean that people will follow all the health guidelines because some highly educated people still lack the awareness to make correct health decisions.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning marital status, the study findings indicated that there was no significant association between MS utilization and marital status. These findings are similar to finding of Abdelaziz et al, (18) and Secginli et al (25) In the present study, education was not significantly associated with MS utilization; Ersin et al, (26) found that there was no difference detected between the educational level and the rate of having mammograms. They concluded that higher education does not mean that people will follow all the health guidelines because some highly educated people still lack the awareness to make correct health decisions.…”
Section: Discussionsupporting
confidence: 92%
“…The present study aimed to determine the preventive behaviors from COVID- 19 Gender was an important variable affecting the preventive behaviors, so that women showed better observance than men probably since they had greater motivation for health than men. In studies on breast cancer screening behaviors, the health motivation was confirmed as an independent variable (16)(17)(18). In a study by Lau et al on the pandemic of H1N1 in women and men in Hong Kong, women had better performance than men in the prevention of the disease (19).…”
Section: Discussionmentioning
confidence: 99%
“…Because perceived susceptibility is also effective in BSE behavior, this group seems ready to participate in screening. Ersin et al (35) and Aker et al (36) have reported that perceived susceptibility is an important factor for getting mammography. However, Baysal and Gözüm (37) have found in their study women with lower perceived susceptibility had no intentions to undergo mammography.…”
Section: Discussionmentioning
confidence: 99%